2017
DOI: 10.1186/s12971-017-0121-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cigarette smoking initiation, cessation, and relapse among U.S. adults: a comparison of two longitudinal samples

Abstract: BackgroundThe tobacco epidemic in the U.S. has matured in the past decade. However, due to rapidly changing social policy and commercial environments, tailored prevention and interventions are needed to support further reduction in smoking.MethodsUsing Tobacco Use Supplement to the Current Population Survey (TUS-CPS) 2002–2003 and 2010–2011 longitudinal cohorts, five smoking states are defined including daily-heavy, daily-light, non-daily, former and non-smoker. We quantified the changes between smoking states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…53 54 In addition, this study expanded previous research findings to include sexual orientation which was a significant predictor (adults only) of tobacco reuptake, with sexual minorities (identifying as gay/lesbian or bisexual) having higher odds of reuptake to tobacco products except smokeless tobacco than those who identified as straight/ heterosexual. In contrast to Yi et al, 9 who found no racial/ ethnic differences in reuptake rates, we found a significant race/ ethnicity effect in adults such that previous non-Hispanic black users were more likely to reuptake any tobacco, specifically all combusted tobacco products, than previous non-Hispanic white users were. However, among youth, racial/ethnic minorities were less likely to reuptake any tobacco use, but race/ethnicity had no significant effect across individual products.…”
Section: Discussioncontrasting
confidence: 99%
“…53 54 In addition, this study expanded previous research findings to include sexual orientation which was a significant predictor (adults only) of tobacco reuptake, with sexual minorities (identifying as gay/lesbian or bisexual) having higher odds of reuptake to tobacco products except smokeless tobacco than those who identified as straight/ heterosexual. In contrast to Yi et al, 9 who found no racial/ ethnic differences in reuptake rates, we found a significant race/ ethnicity effect in adults such that previous non-Hispanic black users were more likely to reuptake any tobacco, specifically all combusted tobacco products, than previous non-Hispanic white users were. However, among youth, racial/ethnic minorities were less likely to reuptake any tobacco use, but race/ethnicity had no significant effect across individual products.…”
Section: Discussioncontrasting
confidence: 99%
“…More non-daily smokers (who smoked at least weekly) were able to sustain abstinence than daily smokers, as in longitudinal studies in other populations [28,30]. In some longitudinal studies (including an American Indian study), this difference was only apparent between non-daily and heavier daily smokers [31][32][33]. In contrast, we found no such difference in making quit attempts, even though we found non-daily smokers were more likely to have made a quit attempt in the year before the baseline survey, and non-daily smokers were more likely to make a quit attempt between the first two waves of the ITC Four Country study [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlight that smoking onset is highest in young adults, compared to adolescent (Thompson et al, 2017) and older adult populations (Yi et al, 2017). Data from the 2002–2003 and 2010–2011 cohort samples of the Tobacco Use Supplement to the Current Population Survey show that the strongest risk factor for cigarette smoking initiation in adults over a one-year follow-up period is having less than a high school education (Yi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the 2002–2003 and 2010–2011 cohort samples of the Tobacco Use Supplement to the Current Population Survey show that the strongest risk factor for cigarette smoking initiation in adults over a one-year follow-up period is having less than a high school education (Yi et al, 2017). Socioeconomic status also influences continued cigarette smoking beyond initiation: in 2003, smoking prevalence among non-college educated young adults aged 18–34 was twice as high as smoking prevalence among college-educated young adults (Green et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation